Australian firms doing business in China - Menzies, Jane (Henry Stewart Talks, 2013)
Australian businesses doing business in China, Australia, China, Australia-China Business Relations, Doing business, International trade, International investment, Chinese cultural issues, Politics in China, Legal issues in China, Entry modes and strategies in China, Internationalization to China, Motivations for entry into China, Planning for entry into China